Diseño del sistema de gestión en seguridad y salud en el trabajo para la microempresa carne a la llanera YIP (2022)
This proposal sought to design a Management System for Safety and Health at work SGSST, through the intervention of various disciplines and with the active participation of all levels of the organization, in order to improve the conditions of work and health of the working population of the company “Carne a La Llanera YIP”, through coordinated actions to promote health, prevention and control of risks, in a way that promotes the well-being of the group and the productivity of the company. The SG-SST includes the planning, organization, execution and evaluation of interventions on Health Conditions and Working Conditions, it includes the practical description of the main elements that make up the Occupational Health and Safety Systems, based on the parameters established by the Ministry of Labor, especially those contemplated in Resolution 0312 of 2019, issued by the Ministry of Labor. The methodology used in this project is a case study, of a descriptive quantitative type, where the diagnostic tool designed by the Antonio José Camacho University Institution was used, to know the current situation of the SG-SST of the company under study. applied the initial evaluation established in Resolution 0312 of 2019, to know the SG-SST standards of the company. Subsequently, the structured survey was applied to know the sociodemographic study of the working population, followed by the use of the Colombian Technical Guide (GTC 45 of 2012), for the identification of hazards, the evaluation and assessment of the existing risks in the company; and finally the action plan was designed through a matrix with 50 established activities. The results of this investigation were the SG-SST for the company, the hazard identification matrix, risk assessment and assessment, and the action plan for the implementation of the management system. It is concluded that when workers receive adequate training, they carry out continuous personal improvement practices and develop a culture of quality prevention, thus minimizing possible occupational diseases and accidents.